the Local Wisdom of Kubu Raya Society and the Implementation in Science Learning - Hairida Hairida; Fitria Arifiyanti; Vientinny Safrilianti; Deby Erwinda; Sri Apriliani; Apricilia Ahmadiyah (STKIP Singkawang, 2019)
Local wisdom of an area is important to be preserved so that the values contained in it can be learned and understood by the younger generation. This study aimed to identify the local wisdom of the society of Kubu Raya Regency, especially those who use peatlands for livelihoods. The results of this identification are associated with the Basic Competencies (KD) of Science Subjects of Junior High School (SMP) in the 2013 curriculum. The subjects of this study were 10 science teachers who teach in Kubu Raya Regency and the society who use peatlands for livelihoods with a purposive sampling technique. Descriptive research methods are used to achieve research objectives. Data collection techniques using observation sheets, interviews, and questionnaires. Research results on the local wisdom of the society of Kubu Raya Regency relating to peatlands were 7 (seven) KD for 7th grade, 2 (two) KD for 8th grade, and 1 (one) KD for 9th grade, science concepts and character values in each KD. Based on expert validation, it can be concluded that there was a match between local wisdom and KD, the concept of Sciences and character values in science subjects of the 2013 curriculum.